THREE APPROACHES OF WORD SENTENCE MEANING IN TRANSLATION OF ENGLISH SLANG WORD INTO INDONESIAN IN THE NOVEL “THE ADVENTURE OF OLIVER TWIST” - Wintia Sunny, Ni Putu (JOURNAL OF LANGUAGE AND TRANSLATION STUDIES, 2015)
The slang expression means coming to democratic atmosphere in language since the meaning embodied is not absolute. It depends upon who uses it, in which group the users belong to, and in what situation slang word occur. Having knowledge of slang, it means the user is bilingual, or even multilingual. The question emerged is how the user of slang employ slang in their daily communication. Their choice of certain slang replacing the standard may have a certain purposes. Therefore, it is really difficult to translate it in Indonesian. How to transfer the meaning of slang that contains senses about culture, habit, and identity of specific group of people is a complex undertaking. The form of English slang used in the novel "The Adventure of Oliver Twist” by Charles Dickens is generally in the form of primary slang. There were sixteen primary slang words uttered by the character in the novel. However, there was only four secondary slang words found in the novel. So the primary slang more common used by the character in novel. There are three approaches that can be used to find the conceptual meaning of word in the process of translation. There are reference theory, componential analysis, and meaning postulate. Kata Slang merupakan expresi demokratis dalam bahasa yang menganduk makna tidak mutlak. Itu tergantuk pada siapa yang menggunakannya, di lingkungan mana penggunanya tinggal, dan dalam situasi seperti apa kata slang itu digunankan. Pengguna slang biasanya bilingual atau bahkan multibahasa. Pertanyaan pun muncul bagaimana kata slang digunakan dalam komunikasi sehari-hari. Pengguna kata slang menggunakan slang untuk mengganti kata-kata standar yang biasa digunakan sehari-hari pastinya memiliki tujuan tertentu.Oleh karena itu sangat sulit untuk menerjemahkan kata slang bahasa Inggris ke bahasa Indonesia. Bagaimana process untuk mentransfer makna kata slang yang berisi tentang budaya, kebiasaan, dan identitas kelompok tertentu orang adalah suatu usaha yang kompleks. Bentuk bahasa slang dalam bahasa Inggris yang digunakan dalam novel "The Adventure of Oliver Twist" oleh Charles Dickens umumnya dalam bentuk kata slang primer. Ada enam belas kata slang utama yang diucapkan oleh karakter dalam novel, namun  hanya ada empat kata slang sekunder yang ditemukan dalam novel. Jadi kata slang primer lebih umum digunakan oleh karakter dalam novel. Ada tiga pendekatan yang bisa digunakan untuk menganalisis kata slang dalam prosess penerjemahan. Ada teori referensi, analisis komponensial,dan makna leksikal.